Effects of Trichoderma and Foliar Fertilizer on the Vegetative Growth of Black Pepper (Piper nigrum L.) Seedlings - Netty Syam; Hidrawati; St. Sabahannur; Akbar Nurdin (International Journal of Agronomy)
Black pepper is a high nutrient-demanding crop; however, high application rates of the chemical fertilizer may give a negative impact on the environment and human health. Coapplication of the chemical fertilizer with biological fertilizers or biological agents is very important to support growth and high yield. This field experiment was carried out to study the effect of Trichoderma harzianum and foliar fertilization on the vegetative growth of black pepper. The study was conducted for 4 months. The research method was arranged in a factorial based on randomized block design (RBD). The first factor was the application of Trichoderma (50 g, 75 g, and 100 g per plant), and the second one was foliar fertilizers (1.0%, 1.5%, 2.0%, and without foliar fertilizer as the control). The treatments were repeated three times. The results showed that the application of both Trichoderma and foliar fertilizer affected the rate of shoot growth, the number of leaves, and the emergence time on black pepper seedlings under the nursery conditions. The application of 50 g/plant of Trichoderma and 1.5% of the foliar fertilizer resulted in 26% longer shoot length and 54% more leaves and accelerated the appearance of shoots 10 days earlier compared to without Trichoderma and the foliar fertilizer.